Morphological Changes in the Mandibles Accompany the Defensive Behavior of Indiana Mite Biting Honey Bees Against Varroa Destructor - Smith, Jada; Cleare, Xaryn L.; Given, Krispn; Li-Byarlay, Hongmei (Frontiers in Ecology and Evolution, 2021)
The honey bee (Apis mellifera) is the most important managed pollinator to sustainable agriculture and our ecosystem. Yet managed honey bee colonies in the United States experience 30–40% losses annually. Among the many biotic stressors, the parasitic mite Varroa destructor is considered one of the main causes of colony losses. Bees’ mite-biting behavior has been selected as a Varroa-tolerant or Varroa-resistant trait in the state of Indiana for more than a decade. A survey of damaged mites from the bottom of a colony can be used as an extended phenotype to evaluate the mite-biting behavior of a colony. In this study, on average, 37% of mites sampled from the breeding stocks of 59 colonies of mite biters in Indiana were damaged or mutilated, which is significantly higher than the 19% of damaged mites found in commercial colonies in the southern United States. Indiana mite biter colonies had a higher proportion of damaged mites, although among the damaged mites, the number of missing legs was not significantly higher. In addition, the morphology of pollen-forager worker bee mandibles was compared by X-ray microcomputed tomography for six parameters in two populations, and a difference was detected in one parameter. Our results provide scientific evidence that potentially explains the defensive mechanism against Varroa mites: structural changes in the worker bee mandibles.